Experiential approaches to professional communication skills training: a grounded theory study: Presenter(s): Michelle OToole, Royal College of Surgeons in Ireland, Ireland. (April 2023) - Collins, Naoise; Eppich, Walter; Doherty, Eva; Condron, Claire; Doyle, Andrea; Sullivan, Clare
Abstract : Background: Simulation training techniques for team communication skills are rarely shared across sectors. Lack of similar language and conceptualisations of what simulation entails creates barriers to shared learning. Cross sector dialogue is needed to remove barriers to curriculum development. The aim of this study is to identify how various professional sectors (healthcare, first responders, teacher training and law) can share learnings in experiential communication training. Methods: Grounded theory (GT) is a common qualitative methodology in health professions education research used to explore the "how", "what", and "why" of social processes" (Eppich et al. 2019). It is a flexible approach that allows researchers to interpret Findings: using an iterative process of coding and constant comparison of the data. Data collection and analysis occurred simultaneously, i.e. a small number of semi-structured interviews were conducted and then analysed, prior to conducting more interviews (Charmaz 2014; Watling and Lingard 2012). Sampling in GT is: 1) purposeful, with non-random participants being selected based on their experiences with the phenomenon being explored and 2) theoretical, meaning that as themes and constructs develop into theory, researchers can adjust the sampling strategy to include more relevant participants. For this study, our sample included educators spanning four professional sectors. GT methodology emphasizes the reflexivity of the researcher as a key element; the researchers aim to make sense of the participants experience from their own perspective, using their own backgrounds, experiences and preconceptions of the subject, in this case simulation training. Findings: Our indings indicate that learning culture influences participants' approach to experiential learning. Training encounters were categorised by how they are designed, implemented, and reflected upon. The language of experiential learning differed greatly between sectors. Discussion: This research identifies the processes by which learning cultures are shaped within communication training across professional sectors, both within and external to healthcare.